Pendampingan Peningkatan Pelayanan Ketenagakerjaan Desa Muyoarjo Berbasis Platform Digital - Wiwik Wahyuni; Indra Febrianto; Robby Wijaya (AMMA : Jurnal Pengabdian Masyarakat, 2023)
This dedication aims to help address employment issues in Muyoarjo Village, Lawanf District, Malang Regency through a simulated implementation of the SIAPkerja Village model. This model is tailored to the characteristics and potential of the Natural Resources (SDA) and Human Resources (SDM) available in the village. Through the mapping process, it was revealed that the village has potential in the agricultural and tourism sectors that can be optimized. Additionally, the human resources in the village also have the potential to apply the SIAPkerja Village model as an alternative to enhance job opportunities among the local community. The SIAPkerja Village program is designed based on the needs and potentials present in the village. The program consists of four scenarios reflecting current employment conditions: 1) incompetent prospective workers with available job opportunities, 2) competent prospective workers with available job opportunities, 3) incompetent prospective workers with unavailable job opportunities, and 4) incompetent prospective workers with available job opportunities. The management of SIAPkerja Village falls under the responsibility of the village government in collaboration with relevant parties. The village government plays a role in supervising program implementation with support from the youth organization (karang taruna) and the village's POKDARWIS (Tourism Awareness and Environmental Care Group) as the implementers of the SIAPkerja Village program.